Populasi dan Keanekaragaman Serangga Penyerbuk di Kebun Kelapa Sawit Desa Rantau Kapas Bukit Paku Kabupaten Batanghari - Hayata Hayata; Nasamsir Nasamsir; Prasetyo Hady Saputro (Jurnal Media Pertanian, 2022)
The presence of pollinatting insect is an unseparated part in oil palm cultivation. The insect population and its diversity   will affect the pollination process that will produce a good   fruit. This study aimed to determine and study the population as well as the species diversity of pollinating insects on smallhoulder oil palm plantations in Rantau Kapas Bukit Paku Village, Batanghari Regency. Unformated Trials  was carried out  as the experimental design and the location was porpusively chosen because there were plants under study and were uniform in  that location.The method used was a descriptive survey method, which deal with  observing the types and numbers of pollinating insects caught at the sample locations in smallholder oil palm plantations aged 6 years. Catching pollinating insects used Kairomix pheromone traps. The results of the study showed that there were 18,301 species of E kamerunicus  and 478 species of Thrips hawaiiensis  pollinated insects were caught, while 378 non-pollinated insects were caught in the oil palm plantation area in the Bukit Paku area. The general morphology of the fruit was Tenera fruit type, with the average of Fresh Fruit Bunch (FFB) weight as 9.4 kg.